2018
DOI: 10.1051/limn/2017029
|View full text |Cite
|
Sign up to set email alerts
|

Thermal response of Moroccan lakes to climatic warming: first results

Abstract: Water temperature plays a primary role in controlling a wide range of physical, geochemical and ecological processes in lakes, with considerable influences on lake water quality and ecosystem functioning. In this paper, we report on the ability of the one-dimensional lake model to simulate the water temperature of Moroccan lakes, i.e., Sidi Boughaba and Sidi Ali lakes, over a 35 yrs period from 1979 to 2014, affected by climate change and based on a freshwater lake model (FLake). During the study periods, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Kangur et al (2013) observed an increase in maximum water temperature in the summer period for Lake Peipsi (Estonia/ Russia). In a broader perspective the response of lakes to climatic changes in this part of Europe is similar to many other cases located in different regions of the world (Austin and Colman, 2007;Hampton et al, 2008;Shimoda et al, 2011;Groß-Wittke et al, 2013;Zhong et al, 2016;Haddout et al, 2018). For instance, for the summer period (July-September) the surface water temperature in the Great Lakes in North America experienced a warming trend at a rate of 1.1 °C dec -1 (Austin and Colman, 2007).…”
Section: Discussionmentioning
confidence: 62%
“…Kangur et al (2013) observed an increase in maximum water temperature in the summer period for Lake Peipsi (Estonia/ Russia). In a broader perspective the response of lakes to climatic changes in this part of Europe is similar to many other cases located in different regions of the world (Austin and Colman, 2007;Hampton et al, 2008;Shimoda et al, 2011;Groß-Wittke et al, 2013;Zhong et al, 2016;Haddout et al, 2018). For instance, for the summer period (July-September) the surface water temperature in the Great Lakes in North America experienced a warming trend at a rate of 1.1 °C dec -1 (Austin and Colman, 2007).…”
Section: Discussionmentioning
confidence: 62%
“…A study by Li et al, (2019) conducted in four lakes in the Yangtze River catchment showed that over the 39-year study period, the surface water temperature increased at a rate of 0.26-0.28°C dec -1 . Mean annual temperatures in the epilimnion in two lakes in Morocco (Sidi Ali and Sidi Boughaba) in the years 1979-2014 increased by 0.198 and 0.013°C dec -1 , respectively (Haddout et al, 2018). It is worth emphasising that the rate of increase in water temperature in Lake Śniardwy was higher than that for air temperatures for the nearby meteorological station in the analogical period.…”
Section: Discussionmentioning
confidence: 87%
“…It is interesting to note that as shown in figure 2(b), the rate of temperature increase in the metalimnion layer was notably higher than that in the epilimnion layer. The temperatures of the epilimnion layer are strongly correlated with air temperature and are directly affected by climate warming (Haddout et al 2018). But the heightened vertical mixing occurring within the epilimnion and metalimnion layers due to warming (Wahl and Peeters 2014) can push the thermocline slightly downward, causing faster warming at the metalimnion layer.…”
Section: Resultsmentioning
confidence: 99%